2021
DOI: 10.3389/fenvs.2021.709922
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Land Use and Hydrological Connectivity Influence Nutrient Retention in Tropical Rivers Receiving Wastewater Treatment Plant Discharge

Abstract: Riparian areas are recognized for their buffering capacity regarding phosphorus and nitrogen from agricultural and urban runoff. However, their role in attenuating nutrient loads of rivers receiving point source nutrient inputs (e.g., from wastewater treatment plants, WWTPs) is still little understood. Here, we investigated whether ammonium (NH4-N), nitrate (NO3-N), and soluble reactive phosphorus (SRP) retention were influenced by the riparian land use in three Brazilian rivers receiving WWTP effluents. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 104 publications
(130 reference statements)
0
4
0
1
Order By: Relevance
“…Another study led by some of the authors of the present paper revealed the influences of riparian vegetation on nutrient attenuation in sub/tropical streams receiving inputs from wastewater treatment plants (WWTPs; for more details, see Finkler et al 2021). Although riparian areas are well recognized for their buffering capacity regarding pollutants from agricultural and urban runoff (e.g., Daniels and Gilliam 1996), their role in attenuating nutrient loads in streams and rivers receiving point source nutrient inputs (e.g., from WWTPs) remains poorly understood.…”
Section: Effects Of Riparian Vegetation On the Attenuation Of Wastewa...mentioning
confidence: 79%
See 1 more Smart Citation
“…Another study led by some of the authors of the present paper revealed the influences of riparian vegetation on nutrient attenuation in sub/tropical streams receiving inputs from wastewater treatment plants (WWTPs; for more details, see Finkler et al 2021). Although riparian areas are well recognized for their buffering capacity regarding pollutants from agricultural and urban runoff (e.g., Daniels and Gilliam 1996), their role in attenuating nutrient loads in streams and rivers receiving point source nutrient inputs (e.g., from WWTPs) remains poorly understood.…”
Section: Effects Of Riparian Vegetation On the Attenuation Of Wastewa...mentioning
confidence: 79%
“…Nutrient retention during the dry (low hydrological connectivity) and wet (high hydrological connectivity) seasons was assessed. Finkler et al (2021) hypothesized that the presence of riparian vegetation in a 100-m buffer would induce mechanisms responsible for either attenuation or mineralization of nutrients due to lateral hydrological connectivity (via overbank flooding). The results indicated that in periods with expected higher connectivity, nitrate and SRP concentrations tended to be lower downstream of the WWTP than in the dry period.…”
Section: Effects Of Riparian Vegetation On the Attenuation Of Wastewa...mentioning
confidence: 99%
“…Nutrient retention during the dry (low hydrological connectivity) and wet (high hydrological connectivity) seasons was assessed. Finkler et al (2021) hypothesized that the presence of riparian vegetation in a 100‐m buffer would induce mechanisms responsible for either attenuation or mineralization of nutrients due to lateral hydrological connectivity (via overbank flooding). The results indicated that in periods with expected higher connectivity, nitrate and SRP concentrations tended to be lower downstream of the WWTP than in the dry period.…”
Section: Effects Of Riparian Vegetation On the Attenuation Of Wastewa...mentioning
confidence: 99%
“…This difference may be attributed to the small riparian zone (i.e., Gleysols, Histosols and Planosols region; Figure 1) in the reference catchment, which results in lower in-stream DOC and higher nitrate concentrations (Stockinger et al, 2014). Riparian zones play a role in nutrient retention as the physical and biogeochemical properties that occur in these ecotones control the fluctuation of water, nutrients and other substances between the hillslopes and the stream (Weigelhofer et al, 2012;Finkler et al, 2021). Thus, riparian zones play an important role in removing nitrate from subsurface flows due to vegetation uptake and increased denitrification (Hill et al, 2014;Hill, 2019) and in C production and storage (Rheinhardt et al, 2012).…”
Section: Spatio-temporal Changes In Doc Nitrate and Dischargementioning
confidence: 99%